Giant low-grade myofibroblastic sarcoma of the male breast: case report and literature review - Shiwei Xiao; Hongtao Chen; Juan Xu; Na Fang; Zirui Ke; Mancheng Yu (Polish Journal of Pathology)
Low-grade myofibroblastic sarcoma is an uncommon malignancy that can be difficult to identify and for which there is no unified treatment protocol. We report herein a case of an 81-year-old male who presented with a giant irregular breast mass and was diagnosed with low-grade myofibroblastic sarcoma. In this study we summarise the clinicopathological features of 13 reported cases of myofibroblastic sarcoma arising in the breast, present the diagnostic process and treatment procedure of our case, and discuss the differential diagnosis from other similar diseases, to provide constructive information and promote deep understanding of myofibroblastic sarcoma in the future.